Glutathione peroxidase‐1 gene rescues cocaine‐induced conditioned place preference in mice by inhibiting σ‐1 receptor expression. (12th August 2019) - Pham, Duc Toan; Chung, Yoon Hee; Mai, Huynh Nhu; Sharma, Naveen; Yun, Jaesuk; Kim, Hee Jin; Cheong, Jae Hoon; Jeong, Ji Hoon; Kim, Dae‐Joong; Shin, Eun‐Joo; Kim, Hyoung‐Chun
Abstract: The aim of this study was to investigate whether the glutathione peroxidase‐1 gene (GPx‐1) affects cocaine‐induced conditioned place preference (CPP) using a mouse model. Cocaine‐induced CPP was accompanied by an increase in the level of σ‐1 receptor in the nucleus accumbens (NAc). This phenomenon was more pronounced in the GPx‐1 gene knockout (GPx‐1 KO) than in wild type (WT) mice. In contrast, the CPP and expression of σ‐1 receptor were much less pronounced in GPx‐1‐overexpressing transgenic (GPx‐1 TG) mice than non‐transgenic (non‐TG) mice. Treatment of the mice withBD1047, a σ‐1 receptor antagonist, significantly attenuated both cocaine‐induced CPP and c‐Fos‐immunoreactivity (c‐Fos‐IR) in WT and GPx‐1 KO mice, although the effects were more evident in the latter group. Despite the protective effects ofBD1047 on cocaine‐induced CPP and c‐Fos in non‐TG mice, there were no additional protective effects in cocaine‐treated GPx‐1 TG mice, indicating that the σ‐1 receptor is a critical target for GPx‐1‐mediated psychoprotective activity. Overall, our results suggest that GPx‐1 attenuates cocaine‐induced CPP via inhibition of σ‐1 receptor expression.